Perubahan Pemanfaatan Lahan Sawah untuk Budidaya Bibit Durian terhadap Tingkat Pendapatan Petani di Desa Alasmalang. - Purwaningsih, Iis; Sidiq, Wahid Akhsin Budi Nur (Edu Geography, 2021)
The changes in the use of paddy fields for durian seed cultivation in Alasamalang village currently widely occurs. This study aimed to determine the driving factors for changes in field used from rice farming to cultivate durian seeds, find out the management of the field for durian seed cultivation, analyze the income of the farmers from the changing fields, and reveal the level of farmers welfare in Alasmalang Village, Kemranjen District. meanwhile for the data analysis, the researcher used percentage descriptive analysis, multiple linear regression and revenue cost ratio (R/C analysis). The results showed that the driving factors for changes in the use of the fields for cultivating durian seeds in Alasmalang Village were influenced by the presence of capital with a percentage of 17%, other successful farmers with a percentage of 16% and fertile land with a percentage of 15%. The results of the calculation of multiple linear regression analysis with the regression equation Y '= 25992.932 + 34.597X1 + 51.492X2 -1.728X3. The simultaneous test/F test is 204,847 with 5% alpha and the number of variables 3 with F table is 2.77, which means the F test> F table and the significance of 0.000> 0.05. It could be concluded that the variables in this study simultaneously affected income. The results of the calculation of revenue cost ratio showed that every Rp. 1 cost incurred would generate revenue of Rp. 9. The level of farmer welfare has increased by 21%. Perubahan pemanfaatan lahan sawah untuk budidaya bibit durian di desa Alasamalang sedang marak terjadi dikalangan para petani. Penelitian ini bertujuan untuk mengetahui faktor pendorong perubahan pemanfaatan lahan sawah dari pertanian padi menjadi budidaya bibit durian, mengetahui pengelolaan lahan sawah untuk budidaya bibit durian dan menganalisis perolehan pendapatan petani dari perubahan pemanfaatan lahan sawah serta mengetahui tingkat kesejahteraan petani di Desa Alasmalang Kecamatan Kemranjen. Teknik analisis data menggunakan analisis deskriptif persentase, analisis regresi linier berganda dan revenue cost ratio (analisis R/C). Hasil penelitian menunjukkan faktor pendorong perubahan pemanfaatan lahan sawah untuk budidaya bubit durian di Desa Alasmalang dipengruhi adanya modal dengan presentase 17 %, melihat petani lain yang berhasil dengan presentase 16 % dan lahan yang subur dengan presentase 15 %. Hasil perhitungan analisis regresi linier berganda dengan persamaan regresi Y’= 25992.932+34.597X1 + 51.492X2 -1.728X3. Pengujian uji simultan/ uji F sebesar 204.847 dengan alpha 5 % dan jumlah variabel 3 dengan F tabel sebesar 2,77 yang artinya uji F > F tabel dan signifikansi 0,000 > 0,05 maka seluruh variabel dalam penelitian ini secara simultan berpengaruh terhadap pendapatan. Hasil perhitungan revenue cost ratio menunjukan bahwa setiap Rp.1 biaya yang dikeluarkan akan menghasilkan penerimaan sebesar Rp. 9. Tingkat kesejahteraan petani mengalami peningkatan 21 %.